EVALUASI KINERJA DAN ANALISIS TINGKAT KEPUASAN PENUMPANG DI STASIUN KRL GROGOL - Jessica Paulina Purba; Christina Sari; Dewi Rintawati (Jurnal Infrastruktur, 2020)
Grogol Station is a Commuter Line KRL Station located on Prof. Dr. Latumenten Street, Jelambar, West Jakarta. This station is included in the small class station and activated in June 2015, but an increase in the number of passengers occurs every year. This indicates that Grogol Station has the potential to be further developed, supported by a strategic location so that many passengers use the KRL Commuter Line in this station. Therefore this study aims to evaluate the performance of services and facilities at Grogol Station and to analyze the level of passenger satisfaction with the services and facilities that have been provided. This study was conducted by direct observation to evaluate the performance of services and facilities at Grogol Station which will be compared with the Minimum Services Standards at PM 63 in 2019. In addition, questionnaires were distributed to analyze the level of passanger satisfaction with the services and facilities provided. The results of the questionnaire will go through validity and reliability tests, then processed using the Importance Performance Analysis (IPA) method. Based on the results of the evaluation, Grogol Station has fulfilled 78,72% of the benchmarks in PM 63 of 2019. From the analysis of the level of the passenger satisfaction, the average value of conformity is still below 100%, that is 77,07%. This means that the performance of services and facilities at Grogol Station is still not as expected, so it does not satisfy the passenger yet. This can be seen from the position of attributes that are still in quadrant A and quadrant C which require treatment to improve their performance.